The Community-Engaged Lab: A Case-Study Introduction for Developmental Science - Liu, Judy; Partington, Scott; Suh, Yeonju; Finiasz, Zoe; Flanagan, Teresa; Kocher, Deanna; Kiely, Richard; Kortenaar, Michelle; Kushnir, Tamar (Frontiers in Psychology, 2021)
Due to the closing of campuses, museums, and other public spaces during the pandemic, the typical avenues for recruitment, partnership and dissemination are now unavailable to developmental labs. In this paper, we show how a shift in perspective has impacted our lab's ability to successfully transition to virtual work during the COVID-19 shut-down. This begins by recognizing that any lab that relies on local communities to engage in human research is itself a community organization. From this, we introduce a community-engaged lab model, and explain how it works using our own activities during the pandemic as an example. To begin, we introduce the vocabulary of mission-driven community organizations and show how we applied the key ideas of mission, vision, and culture to discussions of our own lab’s identity. We contrast the community-engaged lab model with a traditional bi-directional model of recruitment from and dissemination to communities and describe how the community-engaged model can be used to reframe these and other ordinary lab activities. Our activities during the pandemic serve as a case study: we formed new community partnerships, engaged with child “citizen-scientists” in online research, and opened new avenues of virtual programming. One year later, we see modest but quantifiable impact of this approach: a return to pre-pandemic diversity in our samples, new engagement opportunities for trainees, and new sustainable partnerships. We end by discussing the promise and limitations of the community-engaged lab model for the future of developmental research.